A Merged Aldol Condensation, Alkene Isomerization, Cycloaddition/Cycloreversion Sequence Employing Oxazinone Intermediates for the Synthesis of Substituted Pyridines - Williamson, Jill B.; Smith, Emily R.; Scheerer, Jonathan R. (Synlett, 2017)
A domino reaction sequence has been evaluated that begins with union of novel dihydrooxazinone precursors with 2-alkynyl-substituted benzaldehyde components through aldol condensation. Ensuing operations, including alkene isomerization, Diels–Alder, and retrograde Diels–Alder with loss of CO2 occurs in the same reaction vessel to provide polysubstituted tricyclic pyridine products.
Keywords: cycloaddition; cycloreversion; pyridine synthesis; domino reactions; Diels–Alder; oxazinone